Development of neurologic diseases in a patient with primate T lymphotropic virus type 1 (PTLV-1). Issue 1 (December 2016) - Enose-Akahata, Yoshimi; Caruso, Breanna; Haner, Benjamin; Charlip, Emily; Nair, Govind; Massoud, Raya; Billioux, Bridgette; Ohayon, Joan; Switzer, William; Jacobson, Steven
Abstract Background Virus transmission from various wild and domestic animals contributes to an increased risk of emerging infectious diseases in human populations. HTLV-1 is a human retrovirus associated with acute T-cell leukemia and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). HTLV-1 originated from ancient zoonotic transmission from nonhuman primates, although cases of zoonotic infections continue to occur. Similar to HTLV-1, the simian counterpart, STLV-1, causes chronic infection and leukemia and lymphoma in naturally infected monkeys, and combined are called primate T-lymphotropic viruses (PTLV-1). However, other clinical syndromes typically seen in humans such as a chronic progressive myelopathy have not been observed in nonhuman primates. Little is known about the development of neurologic and inflammatory diseases in human populations infected with STLV-1-like viruses following nonhuman primate exposure. Results We performed detailed laboratory analyses on an HTLV-1 seropositive patient with typical HAM/TSP who was born in Liberia and now resides in the United States. Using a novel droplet digital PCR for the detection of the HTLV-1tax gene, the proviral load in PBMC and cerebrospinal fluid cells was 12.98 and 51.68 %, respectively; however, we observed a distinct difference in fluorescence amplitude of the positive droplet population suggesting possible mutations in proviral DNA. A complete PTLV-1 proviral genome was amplified from the patient's PBMC DNA using an overlapping PCR strategy. Phylogenetic analysis of the envelope and LTR sequences showed the virus was highly related to PTLV-1 from sooty mangabey monkeys (smm) and humans exposed via nonhuman primates in West Africa. Conclusions These results demonstrate the patient is infected with a simian variant of PTLV-1, suggesting for the first time that PTLV-1smm infection in humans may be associated with a chronic progressive neurologic disease.